Use of an expenditure reducing model in railway carriage - Lingaitiene, Olga; Lingaitis, Vytautas (Transport, 2006)
Passenger transportation by railway is fast, safe, convenient and affordable for people, but it is usually not profitable for the state. Therefore, making passenger transportation profitable is a task of vital importance. Various calculations are used to optimize this process. The paper considers the problems of economical passenger transportation which may by described by two models: the first model is based on the assessment of income‐expenses of separate services, while the second model is related to the assessment of expenses according to their types.First Published Online: 27 Oct 2010